CRANIAL ULTRASOUND: EFFICIENT SCREENING TOOL FOR EARLY DETECTION OF BRAIN INJURY IN PRETERM INFANTS - Erawati, Dini Rachma; Yueniwati, Yuyun (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Background: Cranial ultrasound becomes an important diagnostic tool to evaluate brain injury in infants. Brain injury is a major complication for preterm birth. The brain injury of preterm infants differs from that of a term infant. Brain injury has correlation with gestational age and mode of delivery.Objective: To analyze the correlation between cranial ultrasound findings with gestational age and mode of delivery and to reveal if cranial ultrasound can be used to detect brain injury in premature infants.Methods: An observational analytic study using cross-sectional design took place in Saiful Anwar Hospital Malang, Indonesia. 38 healthy preterm infants underwent cranial ultrasound examination within the first four day of life. Fisher Exact test was used to analyze the correlation between cranial ultrasound findings with gestational age and mode of delivery.Results: Most of the healthy preterm infants (89.5%) were ≥ 32 weeks gestational age, and 52.6% of samples had caesarean section as their mode of delivery. There were three abnormal findings in cranial ultrasound; increased periventricular echogenic (5.3%), increased parenchym echogenic (5.3%), and indistinguishable of gray-white matter differentiation (5.3%). There was no significant correlation between abnormal cranial ultrasound findings with gestational age and mode of delivery (p= 0.202; p= 0.218).Conclusion: There were abnormal cranial ultrasound findings in some healthy preterm infants despite no significant correlation between ultrasound findings with gestational age and mode of delivery. Cranial ultrasound in preterm infants could become a screening tool for early detection of brain injury.